EXPLANATORY SURVEY ON ORGANIZATIONAL COMMUNICATION CLIMATE AND EMPLOYEE WORK MOTIVATION AT THE REGIONAL REVENUE AGENCY OF BANYUASIN REGENCY SOUTH SUMATRA - Tiara Amelia; Jenny Ratna Suminar; Heru Ryanto Budiana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the effect of organizational communication climate on employee work motivation at the Banyuasin Regency Revenue Agency. Effective communication is important for fostering positive employee attitudes, encouraging participation, and increasing motivation to achieve organizational goals. In the public sector, communication supports employee performance and service quality. This study used a quantitative approach with a descriptive research design, and the research population consisted of 140 civil servants (ASN). The sampling technique was total sampling, and data were collected using a structured questionnaire. Data analysis was performed using multiple linear regression, supported by validity and reliability tests.The results of the study indicate that organizational communication climate has a positive and significant effect on employee work motivation. A good climate, with trust, openness, and supportive leadership contributes to work motivation. It is recommended that organizational leaders strengthen communication practices to improve motivation and organizational effectiveness.